La relación entre la autocompasión y la imagen corporal en mujeres jóvenes y adolescentes - Valle Bayly, Carolina Maria (2022)
The vast majority of women define their value based on their body image. That is because society places great importance on beauty, physical appearance and thinness. The present study seeks to describe the relationship between self-compassion and body image in young and adolescent women. An applied review was conducted under the PRISMA guidelines (Urrutia & Bonfill, 2013), specifying both the eligibility criteria and search strategies, from which the analysis of 10 articles was obtained. The results show a positive relationship between self-compassion and body image; as well as that self compassion can be a protective tool against a negative body image. Practical implications are discussed, such as the fact that the study offers professionals, consultants and to the community in general the dissemination of the concept of self-compassion to be included in therapeutic spaces. Finally, the limitations and suggestions of the present applied review are shared, in which it is exposed that self-compassion has been very much studied as a mediating and moderating variable, so that it motivates future works that carry out studies on the direct relation that self-compassion exerts on body image.